Duchowieństwo parafii w Szadku w XVIII w. w świetle wizytacji kościelnych - Różański, Mieczysław (Biuletyn Szadkowski, 2008)
A list of clergymen serving in Szadek parish in the 18th century can be re-created on the basis of church inspections documents, providing information about priest working there at that time. There are records of seven such inspections, containing information with varying levels of detail, but nevertheless they provide such data as personal information, social descent, when and from whom they took holy orders and the date of starting service in the parish of Szadek. Analysis of this information indicates that all the vicars were of noble descent, and the priests working in the parish combined their pastoral duties with other functions (e.g. in a hospital, or as promoters of brotherhoods).